(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Acne vulgaris is a chronic skin disease with multifaceted cause. The exact etiology and pathogenesis of acne are yet to be established completely and various causative factors are considered as pathogenic mechanisms in the development of this disorder. We designed a study to determine the extent of serum trace elements, macrominerals and antioxidants in patients with acne, and thereby, to find the pathophysiological correlations, if any. Serum trace elements and macro-minerals were determined by flame atomic absorption spectroscopy. RP-HPLC was used to quantify antioxidants. Significantly (p<0.05) decreased level of zinc (1.90±0.06 vs. 2.17±0.09 mg/L), calcium (115.64±4.84 vs. 197.05±7.11 mg/L) and vitamin A (0.2±0.06 vs. 0.86±0.26 ?mol/L) was found in patient when compared with the corresponding controls. This investigation suggests a commendable association between the pathogenesis of acne vulgaris with the reduced level of zinc, calcium and vitamin A which could well be used as a diagnostic tool for acne vulgaris. Dhaka Univ. J. Pharm. Sci. 15(2): 215-220, 2016 (December)